The Role of Jarh wa Ta'dil in Hadith Authentication - Ismail, Nurjannah (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2024)
- The science of Jarh wa Ta'dil plays a pivotal role in the authentication of hadiths, aiding in determining the reliability of narrators. Through comprehensive definitions and classifications, Jarh wa Ta'dil provides a systematic approach to evaluate the integrity and precision of narrators. This study elucidates that Jarh, in its technical sense, refers to identifying characteristics that undermine a narrator’s reliability, while Ta'dil involves affirming qualities that establish a narrator’s trustworthiness. The conditions for scholars performing Jarh and Ta'dil are stringent, requiring profound knowledge, piety, honesty, and a thorough understanding of the causes of Jarh and Ta'dil. Mastery of the Arabic language and the ability to avoid bias are also emphasized to ensure accurate assessments. Methods used by scholars to evaluate narrators include relying on the reputation of narrators among other scholars and recommendations from just individuals. Conflicts between Jarh and Ta'dil are addressed by considering differing scholarly opinions. The study identifies six levels of Ta'dil and six levels of Jarh, which aid scholars in making nuanced judgments about narrators. In conclusion, the science of Jarh wa Ta'dil is indispensable for preserving the authenticity of hadiths, ensuring that only reliable narrations are accepted, and maintaining the integrity of Islamic teachings.